2020
DOI: 10.4236/jgis.2020.125030
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the Dynamics of Land Cover and Land Use in the Lobo River Watershed Upstream of Nibéhibé (Center-West of Côte d’Ivoire)

Abstract: From medium-resolution satellite images (Landsat TM, ETM+ and OLI), the spatial dynamics of land cover and land use are highlighted. The objective of this study is to quantify the evolution of land use in the watershed of the Lobo River upstream of Nibéhibé between 1986 and 2019 in order to analyze the impacts of human activities on the landscape. The study method was based, on the one hand, on the processing of satellite images, for the analysis of the dynamics of land use and, on the other hand, on the CA-Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
1
5
0
1
Order By: Relevance
“…This leads to an increase in agricultural land and a loss of natural vegetation. These same observations were made by [7] in their respective studies of the Lobo River watershed in Nibehibe and the RAMSAR of Grand-Bassam. Indeed, projections made according to the predict a population of 597,680 inhabitants in 2050, which is more than double the current population of the department of Seguela.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…This leads to an increase in agricultural land and a loss of natural vegetation. These same observations were made by [7] in their respective studies of the Lobo River watershed in Nibehibe and the RAMSAR of Grand-Bassam. Indeed, projections made according to the predict a population of 597,680 inhabitants in 2050, which is more than double the current population of the department of Seguela.…”
Section: Discussionsupporting
confidence: 74%
“…These confusions could be explained by the heterogeneity of the study area. Variation in woody cover and the passage of bushfires provide a diversity of spectral signatures relatively close to certain formations during the dry season ( [7] [21] [22] [23]), these authors have conducted similar studies to ours in different areas and have also reported these difficulties. They argue that, the confusions are due to a similarity of spectral responses of some woody formations.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…The YRB is the geographical and ecological area affected by the Yellow River system from its source to the sea (Kouassi et al, 2020;Jian et al, 2022). The mean altitude of the western Heyuan region is over 4000 m, consisting of plenty of high-mountains, with year-round snow covering; The altitude of the central region is loess landform, with serious soil erosion; The east is mainly composed of the Yellow River alluvial plain (Hai-Kun et al, 2020;WangHuang et al, 2021;Zhu et al, 2022).…”
Section: The Current Situation Of Natural Environment In Reb-c In Yrbmentioning
confidence: 99%